Observations of the de Haas-van Alpen Effect in Arsenic - Vanderkooy, John (My University, 1967)
Semimetallic arsenic has been studied by magneto-resistance methods and measurement of the de Haas-van Alphen effect using torque and magneto-thermal measurements. Several modifications have been made in the conventional torque techniques. An important cause of nonlinear effects in the torque experiments is presented and compared to other mechanisms for nonlinearities. The Fermi surface of arsenic as determined experimentally is shown to be in good agreement with recent theoretical calculations which were partially guided by the experiments.
Title: Observations of the de Haas-van Alpen Effect in Arsenic, Author: John Vanderkooy, Location: Thode